Performance and carcass characteristics of different cattle types - Loveday, H.D.; Allen, Dell M.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station, 2011)
Different cattle types were evaluated for growth, feed efficiency, and carcass and meat traits. Hereford (H), Angus (A), Red Poll (RP), Brown Swiss (BS), Gelbvieh (G), Maine Anjou (MA) and Chianina sires were mated artificially to Angus and Hereford cows to obtain different crossbred (X) cattle types. Two calf crops were born in March, April, and May of 1973, and 1974, and weaned when 200 days old. All male calves (787) were castrated, fed out and slaughtered in a commercial plant. Carcasses were graded in the cooler and the right side was transported to KSU for detailed cutout and meat quality evaluations.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Performance; Carcass characteristics; Cattle breeds